2010
DOI: 10.1088/0022-3727/43/20/205203
|View full text |Cite
|
Sign up to set email alerts
|

Plasma chemistry and diagnostic in an Ar–N2–H2 microwave expanding plasma used for nitriding treatments

Abstract: This paper reports on mass spectrometry analysis performed downstream a microwave discharge in Ar-N 2-H 2 gas mixture in nitriding conditions. Investigations are focused on the main simple radicals NH 2 , NH and N, and on the molecular species NH 3 and N 2 H 2 produced. Because of wall desorptions due to catalytic effects, we must develop a specific method taking into account both wall desorption and dissociative ionization effects, in order to correct the mass spectrometer signal intensity. The relative conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Plasma catalysis has thus the potential to provide improved energy efficiency, decreased capital costs, and extended catalyst lifetime. 14 Over the years, the formation of ammonia from nitrogen and hydrogen feed gases has been studied for a wide variety of plasmas from high pressure thermal plasmas [15][16][17][18][19][20][21][22] (lower electron and ion temperatures than in low-pressure plasmas but high gas temperature) to low pressure plasmas [23][24][25][26][27][28][29] (high electron and ion energy).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma catalysis has thus the potential to provide improved energy efficiency, decreased capital costs, and extended catalyst lifetime. 14 Over the years, the formation of ammonia from nitrogen and hydrogen feed gases has been studied for a wide variety of plasmas from high pressure thermal plasmas [15][16][17][18][19][20][21][22] (lower electron and ion temperatures than in low-pressure plasmas but high gas temperature) to low pressure plasmas [23][24][25][26][27][28][29] (high electron and ion energy).…”
Section: Introductionmentioning
confidence: 99%
“…Jang and Lee 29 previously examined a few aspects in an inductively coupled H 2 -N 2 plasma by measuring n e , T e and ion signal intensities. In addition, there exists a variety of studies about H 2 -N 2 plasmas in which the densities of background gas species 13,20,[30][31][32][33] , radicals 7,8,20,32,34 , electrons 34,35 and ion signals 7,36 as well as the surface loss probability of H and N (see Ref. 7 ) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Argon admixtures to hydrogen and nitrogen containing plasmas were examined in the studies of Refs. 20,26,31,35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Jauberteau et al 76 provided estimated reaction coefficients for important recombination processes of atomic and molecular hydrogen with surface-adsorbed NH x species such as NH and NH 2 ; these are important for plasma modeling. Touimi et al 77 reported detailed measurements of N atoms, NH x radicals, and NH 3 and N 2 H 2 molecules in a Ar−N 2 −H 2 plasma used for nitriding. Correlations were examined between the plasma chemistry and plasma parameters (electron density and energy electron distribution function) obtained using spatially resolved Langmuir probe measurements.…”
mentioning
confidence: 99%